The Effect of BI Rate and Exchange Rate on Inflation in Indonesia with the Money Supply as a Mediating Variable - Oktavia, Vicky; Wahyudi, Sugeng (Jurnal Penelitian Ekonomi dan Bisnis, 2022)
Inflation can be interpreted as a tendency to increase the prices of goods and services in general and continuously which can be influenced by several factors such as reference interest rates, exchange rates, the money supply and so on. This study intends to analyze about the influence of the BI rate and the exchange rate on inflation in Indonesia with the money supply as an intervening variable. The population in this study is Inflation, BI Rate, Rupiah / USD Exchange Rate, and Money Supply. The sample used is this data in the 2010-2019 period which was analyzed using WarpPLS and Sobel Test. The results show that the BI rate, exchange rate and the money supply have a significant effect on inflation and the money supply can mediate the effect of the BI rate and the exchange rate on inflation which has been proven by the sobel test. Keywords:InflationBI RateExchange RateMoneySupply